Coupling between serotoninergic and noradrenergic neurones and γ-motoneurones in the cat - Gladden, M H (Blackwell Science Inc, 2000)
1. Noradrenaline is known to suppress transmission from group II muscle afferents when locally applied to γ-motoneurones, and serotonin (5-HT) facilitates the transmission. The purpose of this investigation was to search for evidence of monoaminergic innervation of γ-motoneurones. 2. Eight γ-motoneurones were labelled with rhodamine-dextran, and 50 μm thick sagittal sections of the spinal cord containing them were exposed to antibodies against dopamine β-hydroxylase (DBH) and 5-HT. All the cells were directly and/or indirectly excited by muscle group II afferents from the muscle they innervated and/or other muscles. 3. Appositions between monoaminergic fibres and the labelled somata and dendrites were located with three-colour confocal laser scanning microscopy by examining series of optical sections at 1 or 0.5 μm intervals. 4. DBH and 5-HT varicosities formed appositions with the somata and dendrites of all the γ-motoneurones. The mean packing densities for 5-HT (1.12 ± 0.11 appositions per 100 μm(2) for somata and 0.91 ± 0.07 per 100 μm(2) for dendrites) were similar to the densities of contacts reported for α-motoneurones. Monoaminergic varicosities in apposition to dendrites greatly outnumbered those on the somata. 5. The density of DBH appositions was consistently lower – corresponding means were 53 % and 62 % of those for 5-HT on the somata and dendrites, respectively. 6. It is concluded from an analysis of the distribution and density of varicosities in apposition to the γ-motoneurones compared with the density in the immediate surround of the dendrites that there is indeed both a serotoninergic and noradrenergic innervation of γ-motoneurones.